Civil society promoting government accountability for health equity in the Caribbean: The Healthy Caribbean Coalition - Trevor A. Hassell; Maisha T. Hutton; D. Beverley Barnett (Pan American Health Organization, 2020)
Achieving health equity and addressing the social determinants of health are critical to attaining the health and health-related targets of the 2030 Agenda for Sustainable Development and its Sustainable Development Goals. Frameworks for health, including the Sustainable Health Agenda for the Americas 2018 - 2030, emphasize reduction of health inequities and "leaving no one behind" in national sustainable development. Health equity includes advancing universal health and the primary health care approach, with equitable access for all people to timely, quality, comprehensive, people- and community-centered services that do not cause impoverishment. Equally important, and a hallmark of good governance, is accountability for such advances. Governments have primary responsibility for reducing health inequities and must be held accountable for their policies and performance. Civil society has been recognized as a key partner in advancing sustainable and equitable national development. Effective accountability mechanisms should include civic engagement. The Healthy Caribbean Coalition (HCC), the only Caribbean regional alliance of civil society organizations working to prevent and control noncommunicable diseases-a major health priority fueled by inequities-has played a significant role in holding governments accountable for advancing health equity. This case study examines factors contributing to the success of the HCC, highlighting work under its five strategic pillars-accountability, advocacy, capacity development, communication, and sustainability-as well as challenges, lessons learned, and considerations for greater effectiveness.